An efficient and practical radiosynthesis of [(11)C]temozolomide - Moseley, Christian K. (2012)
[Image: see text] Temozolomide (TMZ) is a prodrug for an alkylating agent used for the treatment of malignant brain tumors. A positron emitting version, [(11)C]TMZ, has been utilized to help elucidate the mechanism and biodistribution of TMZ. Challenges in [(11)C]TMZ synthesis and reformulation make it difficult for routine production. Herein we report a highly reproducible one-pot radiosynthesis of [(11)C]TMZ with a radiochemical yield of 17±5% and >97% radiochemical purity.